Suspended Evidence: Rethinking the Photographic (Cinéma & Cie. Film and Media Studies Journal, 2015)
Though the post-media condition erases their specificity, cinema and photography, in their mutual dynamic, have reappeared overwhelmingly in contemporary media practices and theoretical reflection, specifically since a renewed interpretation of the still-moving dialectic has become a crucial dimension of the contemporary image. Therefore exchanges, overlaps and bonds between the filmic and the photographic categorize the prevailing paradigm not only in the analysis of the new forms of the image, but also in reinterpreting the history of the two media and of their earliest and perpetual intersection. The historical reconsideration of the connection between cinema and photography demands clarity in some grey areas that so far have been neglected, such as film stills, analysed in the following essay. They constitute a complex dispositif of exchange between cinema and photography, and not by chance are central to much innovative research on the photographic. Historical analysis and visual experimentation have progressed in parallel, both interested in a ‘return to the past’: to the origin of our gaze, but also to a different relationship with images. Hence, having first identified the necessity to adopt a perspective on media relations based on confluence instead of influence, the essay deals with two symptomatic forms of confluence between cinema and photography. First, a form of ‘compressed cinema’ that gives up on time and on the flow of the images and instead is condensed within a single photograph (like in Gregory Crewdson’s works); second, a sort of suspended photography, that takes on the incompleteness, the dynamism and the temporality of cinema, thus transcending its boundaries (as in Linda Fregni Nagler’s Pour commander à l’air).